Pattern formation in neural dynamical systems governed by mutually Hamiltonian and gradient vector field structures - Gafiychuk, V.V.; Prykarpatsky, A.K. (Condensed Matter Physics, 2004)
We analyze dynamical systems of general form possessing gradient (symmetric)
and Hamiltonian (antisymmetric) flow parts. The relevance of such
systems to self-organizing processes is discussed. Coherent structure formation
and related gradient flows on matrix Grassmann type manifolds are
considered. The corresponding graph model associated with the partition
swap neighborhood problem is studied. The criterion for emerging gradient
and Hamiltonian flows is established. As an example we consider nonlinear
dynamics in a neuron network system described by a simulative vector
field. A simple criterion was written in order to establish conditions for the
formation of an oscillatory pattern in a model neural system under consideration. Аналізуються динамічні системи загального виду, векторні поля яких складаються з градієнтної (симетричної) та Гамільтонової (антисиметричної) складових. Дискутується відповідність таких систем процесам самоорганізації. Розглядається виникнення когерентних структур і відповідних градієнтних потоків на грасманових многовидах, а також моделювання таких структур відповідною моделлю графа, який виникає в результаті такого формування. Встановлено критерій виникнення гамільтонових і градієнтних векторних полів. Розглядається модельний приклад нейронної динамічної системи, для якої встановлені умови виникнення осциляційних структур.